The Language of Diplomacy: A Sociolinguistic Analysis of Global Reactions to the Iran-Israel Conflict and Their Role in Shaping Peace and Conflict Narratives - Javeria Shaukat; Khadija Iqtidar; Kaukab Saba, (ASIAN Journal of International Peace & Security (AJIPS), 2024)
This study delves deep into the sociolinguistic analysis of how the international perspectives of peace and conflicts are shaped by the diplomatic language specifically in the recent Iran-Israel conflict in October 2024. By focusing on the official statements issued by United States, Russia, and Turkey, the research paper explores how world powers use discourse to position themselves, manage global perceptions, and either mediate or intensify geopolitical tensions. The study utilizes the Norman Fairclough’s three-dimensional model of Critical Discourse Analysis (CDA) as the framework for analyzing diplomatic language in the Iran-Israel conflict. It involves linguistic descriptivism i.e. text analysis, interpretation and explanation. By situating the Iran-Israel conflict within a sociolinguistic framework, the research highlights how diplomacy is not merely about policy, but about the strategic use of language. The findings reveal distinct patterns in how peace and conflict are discursively constructed, offering new insights into the intersection of linguistics, politics, and international relations.